COOPERATIVE LEARNING "ROLE PLAYING" IN NUR IHSAN ISLAMIC FULL DAY SCHOOL - Ayu Sahara Tumanggor; Novita Sari Lubis; Rika Muliana Tanjung; Sari Sekar Wangi; Indayana Febriani Tanjung (ATRIUM PENDIDIKAN BIOLOGI, 2022)
The purpose of the study was to determine the ability of high school students during learning using the role-playing method, and the most important thing was to train their abilities as prospective teachers. This research is self-assessment, using instruments in the form of student worksheets, cameras and stationery, PPT, and other supporting equipment. Data analysis with quantitative and qualitative methods. We conclude that this model is very effective.